If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-10 + -1x) = -4 (-10 * -2 + -1x * -2) = -4 (20 + 2x) = -4 Solving 20 + 2x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 2x = -4 + -20 Combine like terms: 20 + -20 = 0 0 + 2x = -4 + -20 2x = -4 + -20 Combine like terms: -4 + -20 = -24 2x = -24 Divide each side by '2'. x = -12 Simplifying x = -12
| 0.5t+5=1 | | -0.25*cos(x)+4*cos(2x)+2.25*cos(3x)+0.25*cos(4x)=0 | | 6-2(x+5)=18-x | | y-7=0.7/2(x-5.2) | | 10x-4+5x+79=90 | | 2.8-y=6.9 | | (x+7)4=48 | | 3x-13+3x-10=12x-6 | | 56q^2-19qt-15t^2=0 | | 4(3x-3)=96 | | x*0.7=10 | | 6-5(7m+5)=86 | | 2x+3+x=x+3 | | 18q^2-39qt-189t^2=0 | | 6x-1x=6-6 | | 2i/3i | | 2w+2(1w+283)=19 | | 5p-95p+119p-p=151 | | 3[x+5]=27 | | 8x^2+10x+25= | | 2(3a+1)=5(a-1) | | 66-2r+1=3r-5(r-2) | | F(10.5)= | | 28+x=14 | | 6=x-3/2 | | 2(p+5)-3(p-7)=43 | | (9x^7)(-8x^5)=0 | | 10(d+9)=210 | | 7x-7-5x=2 | | 40-[3c+4]=4[c+5]+c | | 40-[3c+4]=[c+5]+c | | 4m-3=6m+5 |